Preparation method of high-performance sulfide electrolyte and all-solid-state battery

By mixing sulfide electrolytes with lithium salt, after grinding, suppression and thermal treatment, to form a high -performance vulcanizing electrolyte, solve the problem of poor matching of the existing electrolyte and lithium metal negative electrode, and realize a full solid -state battery with high energy density and stability. Essence

CN119381538APending Publication Date: 2025-01-28BEIJING INST OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411688913.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing sulfide electrolyte has poor matching with the lithium metal negative electrode, and there are problems such as spontaneous interface reaction and lithium dendrites penetration, resulting in unstable battery performance, complex preparation process and high cost.

Method used

By mixing the electrolytes of the original sulfide with lithium salt, it has been grinded, suppressed and thermal treatment, and a high -performance vulcanization electrolyte is formed. This method is performed in an inert atmosphere to ensure that lithium salts are evenly distributed and wrapped with vulcosine electrolyte particles, and the electrolyte ion conductivity and interface stability are improved.

Benefits of technology

The high -chamber temperature ion conductivity, low -electronic conductivity and good lithium negative matching properties are achieved, which improves the energy density and cycle stability of all -solid -state batteries, and reduces the problem of lithium -branch crystal growth and decreased conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381538A_ABST
    Figure CN119381538A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid batteries, in particular to a preparation method of a high-performance sulfide electrolyte and an all-solid-state battery. The method comprises the following steps: mixing an original electrolyte and a lithium salt, grinding, pressing, carrying out heat treatment, and grinding into powder, so that in the obtained sulfide electrolyte, the original electrolyte and the lithium salt are uniformly distributed, part of the lithium salt permeates into crystal lattices of the original sulfide electrolyte, and sulfide electrolyte particles are wrapped by the residual lithium salt. The obtained sulfide electrolyte has high room-temperature ionic conductivity and low electronic conductivity, and has good interface compatibility when being matched with lithium metal, so that an all-solid-state battery with high energy density can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid batteries, and in particular to a method for preparing a high-performance sulfide electrolyte and an all-solid-state battery. Background Art

[0002] As one of the important technologies in the field of new quality productivity energy, lithium-ion batteries have played a huge role in changing transportation, energy storage, electronic products, etc., so batteries have become a necessity in modern life. With the rapid development of society, the energy density and safety of the current liquid battery system have caused people's anxiety. Solid-state system batteries are born for application, in which solid electrolytes replace carbonate liquid electrolytes, helping batteries achieve higher energy density and safety.

[0003] Among many solid electrolytes, sulfide electrolytes have high ionic conductivity comparable to that of liquid electrolytes, and their own advantages such as high plasticity and easy processing and molding make them stand out. Their development has received widespread attention from academia and industry. However, the electrolyte has poor compatibility with high-energy-density lithium metal negative electrodes, and spontaneous interface reactions generate impurity phases with low ion and high electron conductivity. In particular, the electrolyte's own non-negligible electronic conductivity and grain boundary and structural defects cause lithium dendrites to penetrate the electrolyte and cause short circuits. Patent CN117497836A proposes a solid electrolyte material, its preparation method and application, by coating a layer of halide LiTaCl5M on the surface of the sulfide electrolyte core. 1 / n (M=Cl, F, I, Br or O), using the characteristics of high stability and high ionic conductivity of halide electrolytes for high-voltage positive electrode materials, the electrolyte can maintain high conductivity while taking into account the purpose of achieving a higher oxidation potential, greatly improving the stability of the target electrolyte to the high-voltage positive electrode. However, the preparation process of the electrolyte is complicated, involving the mixing of two or more electrolytes and liquid phase treatment, and the solvent may cause structural damage to the sensitive and polar sulfide electrolyte. The residual solvent is difficult to control, and the problem of ion mutual diffusion cannot be avoided during the liquid phase and heat treatment process; at the same time, the electrolyte has poor matching with the lithium negative electrode, and the high-priced tantalum ions (+5) are easily reduced by lithium metal to form an alloy phase, resulting in interface failure and performance degradation, and there are also problems such as high cost and difficulty in commercial use; Patent CN114933331B proposes a sulfide solid electrolyte and a preparation method, which improves the compatibility with the lithium series negative electrode and better electrochemical stability by replacing V, Nb, and Ta in the P position, thereby improving the cycle stability of the sulfide all-solid-state battery. However, element doping has high requirements on process and is only applicable to laboratory scale. At the same time, the effect of doping on improving lithium negative electrode is relatively poor. The metal oxide phase formed will hinder ion transport, and this type of electrolyte cannot avoid the problem of lithium dendrite growth; it also causes a decrease in conductivity, and the assembled battery has poor rate performance.

[0004] Therefore, developing high-performance sulfide electrolytes is one of the key directions of all-solid-state batteries. In view of the lack of effective means to improve ionic conductivity, reduce electronic conductivity, and match lithium metal negative electrodes, the present invention is specially proposed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the first technical solution of the present application discloses a method for preparing a high-performance sulfide electrolyte, comprising:

[0006] mixing a sulfide and a lithium salt to obtain a mixture;

[0007] pressing the mixture into a sheet-like mixed solid;

[0008] The flaky mixed solid is subjected to heat treatment and then subjected to grinding treatment to obtain a high-performance sulfide electrolyte;

[0009] Wherein, the above steps are all carried out under an inert atmosphere.

[0010] Furthermore, the original sulfide electrolyte is selected from one or more of lithium argyrodite-type electrolyte (Li6PS5Cl or Li6PS5Br), lithium germanium phosphorus-sulfur type electrolyte (Li10GeP2S12 or Li10SiP2S12), and glass-ceramic electrolyte (Li7P3S11 or Li3PS4), and the lithium salt is a halogen lithium salt.

[0011] Preferably, the lithium salt is one or more of lithium chloride, lithium fluoride, lithium bromide and lithium iodide.

[0012] Furthermore, in the mixture, the molar percentage of the original sulfide electrolyte is 25% to 91%, and the molar percentage of the lithium salt is 19% to 75%.

[0013] Preferably, in the mixture, the molar percentage of the original sulfide electrolyte is 33.3% to 66.7%, and the molar percentage of the lithium salt is 33.3% to 66.7%.

[0014] Furthermore, the mixing method of the original sulfide and the lithium salt includes ball milling, and the ball milling speed is ≥100 rpm / min and the time is ≥20 minutes.

[0015] Furthermore, the pressing pressure of the mixture is 100-500 MPa.

[0016] Furthermore, the mixed solid heat treatment temperature is 200-600° C., and the treatment time is 0.5-6 hours.

[0017] And, a high-performance sulfide electrolyte prepared according to the above preparation method.

[0018] The second technical solution of the present application discloses an all-solid-state battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is a high-performance sulfide electrolyte prepared by the first technical solution.

[0019] The beneficial effects of the present invention are as follows: the present invention mixes the original electrolyte with the lithium salt, grinds it into powder after grinding, pressing and heat treatment, so that the original electrolyte and the lithium salt are evenly distributed in the obtained high-performance sulfide electrolyte, part of the lithium salt penetrates into the original sulfide electrolyte lattice, and the remaining lithium salt wraps the sulfide electrolyte particles. On the one hand, because the lithium salt contains halogen atoms, the diversity of the anion sublattice structure of the original electrolyte is improved, the ion migration barrier is reduced, thereby improving its ion transmission capacity, that is, improving the electrolyte ion conductivity; on the other hand, the unreacted lithium salt is wrapped on the surface of the original electrolyte particles to form a coating layer, and the low electronic conductivity of the lithium salt can effectively prevent electrons from attacking the original sulfide electrolyte, improve the interface stability on the positive electrode side, and because the original sulfide electrolyte is wrapped by the halide, the electronic conductivity of the grain boundary is reduced, which is conducive to hindering the growth of dendrites at the lithium negative electrode / electrolyte interface, reducing the strong reduction effect of lithium metal on the sulfide electrolyte, and matching the lithium negative electrode; further, the coating layer is also conducive to isolating water molecules in the air, improving the air stability of the electrolyte. The resulting high-performance sulfide has high room-temperature ionic conductivity, low electronic conductivity, and good interfacial compatibility with lithium metal, thereby obtaining a high-energy-density all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The neutron diffraction pattern and Rietveld refinement results of the solid electrolyte prepared in Example 1;

[0021] Figure 2 The SEM and element distribution mapping of the solid electrolyte prepared in Example 1;

[0022] Figure 3 The electrochemical impedance spectrum of the solid electrolyte prepared in Example 1;

[0023] Figure 4 This is a fitting diagram of the polarization current curve of the solid electrolyte prepared in Example 1;

[0024] Figure 5 This is a fitting diagram of the polarization current curve of the solid electrolyte prepared in Comparative Example 1;

[0025] Figure 6 The cyclic voltammetry curve of the solid electrolyte prepared in Example 1;

[0026] Figure 7 The cyclic voltammetry curve of the solid electrolyte prepared in Comparative Example 1;

[0027] Figure 8 The voltage (current)-time curve of the solid electrolyte assembled lithium symmetric battery prepared in Example 1 during deposition and stripping;

[0028] Fig. 9 The maximum voltage and time curve during deposition and stripping of the solid electrolyte assembled lithium symmetric battery prepared in Example 1;

[0029] Fig.10 The first cycle charge and discharge curve of the solid electrolyte assembled half-cell prepared in Example 1;

[0030] Fig.11 This is the first cycle charge and discharge curve of the solid electrolyte assembled half-cell prepared in Comparative Example 1. DETAILED DESCRIPTION

[0031] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art, but it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the present invention are protected. The experimental methods in the following examples that do not specify specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.

[0032] The first embodiment of the present application discloses a method for preparing a high-performance sulfide electrolyte, comprising:

[0033] mixing a sulfide electrolyte and a lithium salt to obtain a mixture;

[0034] pressing the mixture into a sheet-like mixed solid;

[0035] The flaky mixed solid is subjected to heat treatment and then subjected to a second grinding treatment to obtain a high-performance sulfide electrolyte;

[0036] Wherein, the above steps are all carried out under an inert atmosphere.

[0037] In this embodiment, the purpose of the mixing is to evenly distribute the original sulfide electrolyte and the lithium salt. It can be understood that, in order to achieve this purpose, solid phase mixing can be carried out by hand grinding, ball milling, etc.; when the liquid phase method is adopted, low polarity or non-polar solvents such as dichloromethane, n-heptane, p-xylene, trimethylolbenzene, anisole, monochlorobenzene and cyclohexanone are used to dissolve the raw materials, and after sufficient mixing, they are dried to obtain a solid mixture, and then enter the subsequent procedures.

[0038] In order to reduce the number of steps and the risk of introducing impurities in the solvent, the preferred embodiment of the present application selects solid phase mixing, that is, the original sulfide electrolyte solid and the lithium salt solid are ground and mixed, and the grinding is preferably ball milling. When ball milling is used, the ball milling speed is ≥100rpm / min and the time is ≥20 minutes.

[0039] Furthermore, the original sulfide electrolyte is selected from one or more of lithium argyrodite-type electrolyte (Li6PS5Cl or Li6PS5Br), lithium germanium phosphorus-sulfur type electrolyte (Li10GeP2S12 or Li10SiP2S12), and glass-ceramic electrolyte (Li7P3S11 or Li3PS4), and the lithium salt is a halogen lithium salt.

[0040] It can be understood that in this embodiment, the original sulfide electrolyte is a sulfide electrolyte disclosed in the prior art, preferably the above components, more preferably a lithium sulfide silver germanium ore type, glass ceramic electrolyte, and most preferably a Li6PS5Cl electrolyte; the lithium salt is a halogen lithium salt, that is, a lithium salt composed of halogen ions as anions and lithium ions as cations, and its purpose is to introduce halogen atoms into the sulfide electrolyte during the mixing process. The presence of halogen atoms can increase the diversity of the anion sublattice structure of the original electrolyte, thereby reducing the ion migration barrier and improving the ion transmission capacity, that is, improving the electrolyte ion conductivity, and because the original sulfide electrolyte is wrapped by the halide, it is beneficial to hinder the growth of dendrites at the lithium negative electrode / electrolyte interface, reduce the strong reduction effect of lithium metal on the sulfide electrolyte, and match the lithium negative electrode. The halogen lithium salt of the present application is preferably one or more of lithium chloride, lithium fluoride, lithium bromide, and lithium iodide, more preferably lithium chloride, lithium fluoride, and lithium bromide, and most preferably lithium chloride.

[0041] Furthermore, in the mixture, the molar percentage of the original sulfide electrolyte is 25% to 91%, and the molar percentage of the lithium salt is 19% to 75%.

[0042] Preferably, in the mixture, the molar percentage of the original sulfide electrolyte is 33.3% to 66.7%, and the molar percentage of the lithium salt is 33.3% to 66.7%.

[0043] In this embodiment, the purpose of the above ratio is mainly to coordinate the ratio of the sulfide electrolyte to the remaining lithium salt content. The main ion transmission path of the present invention is through the sulfide electrolyte, and the remaining lithium salt provides some active lithium ions to enhance the electrolyte ion transmission. If the proportion of lithium salt increases, the non-lithium ion active medium in the sulfide electrolyte is increased, which is not conducive to ion conduction; if the proportion of lithium salt is too small, it cannot play its role in protecting the sulfide electrolyte, and its ability to shield electrons and air stability are reduced.

[0044] In some specific embodiments, the mixture is pressed at a pressure of 100-500 MPa.

[0045] In some specific embodiments, the mixed solid is heat treated at a temperature of 200-600° C. and a treatment time of 0.5-6 h.

[0046] Example 1

[0047] A novel high-performance sulfide solid electrolyte is prepared by the following steps;

[0048] (1) In an argon atmosphere glove box, 2.684 g of Li6PS5Cl argyrodite electrolyte and 0.424 g of LiCl lithium salt were weighed, with molar percentages of 50% and 50%, and manually ground in a mortar for 15 minutes. The mixture was added to a ball mill and ball milled at a rotation speed of 300 rpm for 30 minutes to obtain a solid powder mixture;

[0049] (2) In an argon atmosphere glove box, the powder mixture was pressed into a dense disc at a pressure of 300 MPa;

[0050] (3) The disc was calcined at 400°C for 2 hours in an argon atmosphere and manually ground into powder after heat treatment to obtain a sulfide solid electrolyte.

[0051] The neutron diffraction spectrum of the sulfide solid electrolyte prepared in this example is shown in Figure 1. Through Rietveld refinement, the contents of argyrodite-type electrolyte and lithium chloride salt are 83.1% and 16.9%, respectively, and no other impurity phases are produced, proving that a new type of high-performance sulfide electrolyte has been successfully prepared.

[0052] The scanning electron microscope image and element distribution of the high performance sulfide solid electrolyte prepared in this example are shown in FIG. Figure 2 As shown, the argyrodite-type electrolyte particles are 4 to 6 microns, the lithium chloride particles are 100 to 300 nanometers, and the lithium chloride is wrapped around the argyrodite-type electrolyte particles.

[0053] Example 2

[0054] A novel high-performance sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (1), 2.684 g of Li6PS5Cl argyrodite-type electrolyte and 0.848 g of LiCl lithium salt were weighed, with molar percentages of 33.3% and 66.7%, respectively, and in step (3), the wafer was calcined at 300° C. for 3 hours in an argon atmosphere.

[0055] Example 3

[0056] A novel high-performance sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (1), 3.128 g of Li6PS5Br argyrodite-type electrolyte and 0.434 g of LiBr lithium salt were weighed, with molar percentages of 66.7% and 33.3%, respectively, and in step (3), the wafer was calcined at 400° C. for 5 hours in an argon atmosphere.

[0057] Example 4

[0058] A novel high-performance sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (1), 0.36 g of Li3PS4 glassy electrolyte and 0.267 g of LiI lithium salt were weighed in molar percentages of 50% and 50%, and in step (3), the wafer was calcined at 400°C for 5 hours in an argon atmosphere.

[0059] Example 5

[0060] The novel high-performance sulfide solid electrolyte was prepared by the same process as in Example 1, except that in step (1), 2.684 g of Li6PS5Cl argyrodite electrolyte and 0.669 g of LiI lithium salt were weighed, with molar percentages of 66.6% and 33.3%, respectively.

[0061] The novel high-performance sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (3), the wafer was calcined at 500° C. for 1 hour in an argon atmosphere.

[0062] Comparative Example 1

[0063] The novel high-performance sulfide solid electrolyte was prepared by the same process as in Example 1, except that 2.684 g of Li6PS5Cl argyrodite-type electrolyte was weighed in step (1), with a molar percentage of 100%.

[0064] Comparative Example 2

[0065] The novel high-performance sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (3), the wafer was calcined at 800° C. for 2 hours in an argon atmosphere.

[0066] Comparative Example 3

[0067] The novel high-performance sulfide solid electrolyte was prepared by the same process as in Example 1, except that 0.424 g of LiCl lithium salt was weighed in step (1), and the molar percentage was 100%.

[0068] Test Example 1

[0069] The impedance of the electrolytes obtained in Examples 1 to 5 and Comparative Examples 1 to 3 was measured using AC impedance technology, and the corresponding ionic conductivity was calculated. The test temperature was 0 to 70°C, the test frequency was 0.01 to 106 Hz, and the test instrument used was Metrohm Autolab (PGSTAT302N). According to the thickness (L) of the electrolyte, the area (S) of the stainless steel sheet, and the impedance (R) of the electrolyte, the ionic conductivity of the electrolyte was calculated by the formula σ=L / (S*R). The EIS of Example 1 is as follows: Figure 3 As shown, the ionic conductivity is calculated to be 7.9 mS cm -1 The test results of all samples are shown in Table 1. It can be seen from the table that the conductivity of the high-performance electrolytes of all embodiments is significantly improved compared with the comparative samples. The added lithium salt has a significant positive effect on the ionic conductivity of the original sulfide electrolyte. The conductivity of the electrolyte not synthesized by the present technical solution is affected by the composition and temperature, and its ion transmission capacity is relatively low.

[0070] Table 1 Ionic conductivity test results

[0071]

[0072]

[0073] Test Example 2

[0074] Polarization current curves were used to measure the electronic conductivity of the novel electrolytes obtained in Example 1 and Comparative Example 1. The polarization voltages were 0.2, 0.3, 0.4, and 0.5 mV, respectively. The steady-state current density was measured and linear fitting was performed. Figure 4 and Figure 5 As shown, the calculated electronic conductivity of the electrolyte is 8.8×10 -9 S cm -1 and 2.5×10 -8 S cm -1 , the electronic conductivity of the electrolyte is reduced, thanks to the lithium chloride coating layer that isolates the electronic conduction.

[0075] Test Example 3

[0076] The new electrolyte and acetylene black were mixed in a mass ratio of 9:1 to prepare electrodes, which were assembled into half-cells. The anti-oxidation and reduction ability of the electrolyte was tested by linear sweep voltammetry, with a scanning voltage range of 0-5V vs Li / Li+ and a scanning rate of 0.1mV / s. The test results of Example 1 and Comparative Example 1 are as follows: Figure 6 and Figure 7As shown, no obvious redox peaks were found on the voltammetric curve of the electrolyte obtained in Example 1, indicating that the electrolyte has strong anti-redox ability and a wide electrochemical stability window. On the contrary, the voltammetric curve of the electrolyte obtained in Comparative Example 1 showed four obvious oxidation peaks and two reduction peaks. In this voltage range, the electrolyte underwent obvious decomposition reaction.

[0077] Test Example 4

[0078] The electrolyte obtained in Example 1 was sandwiched between two pieces of lithium metal to construct a Li||Li symmetrical battery. The constant current charge and discharge test was used to evaluate the lithium stability of the electrolyte in the battery. The test instrument used was Land CT2001A, the test temperature was 30°C, and the test results were as follows: Figure 8 As shown in the figure, it can be seen that the Li||Li symmetric battery assembled with the solid electrolyte in Example 1 has a high -2 The deposition and stripping can last for 220 hours without short-circuit failure at a current density of , and the electrolyte and lithium metal have good interface stability.

[0079] Furthermore, the charge and discharge curves of the symmetrical battery at different current densities were tested to determine its critical current density. The results are shown in the attached figure. Fig. 9 As shown, it can be seen that the critical current density of the solid electrolyte is 1.6 mA cm -2 , indicating that the electrolyte can be charged and discharged at a larger current.

[0080] Test Example 5

[0081] The electrolytes obtained in Example 1 and Comparative Example 1 were respectively assembled into LCO||Li batteries in an argon glove box with H2O < 0.1 ppm and O2 < 0.1 ppm, and charge and discharge tests were performed using Land CT2001A with a voltage range of 2.5 to 4.2 V and a temperature of 30°C.

[0082] The charge and discharge curves of the obtained LCO||Li battery are as follows: Fig.10 and 11 As shown in the figure, it can be seen that the solid electrolyte obtained in Example 1 is -1 ) showed excellent electrochemical performance at a charge and discharge rate of 1.5 % and a discharge capacity of 125.6 mAh g -1 After 580 cycles, the discharge specific capacity is 59.6 mAh g-1, which has good electrochemical stability; while the electrolyte of comparative example 1 has almost no capacity when it is cycled less than 40 times, and its cycle stability is significantly lower than that of example 1.

[0083] And, a high-performance sulfide electrolyte prepared according to the above preparation method. Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it; although the present invention is described in detail with reference to the above embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features thereof can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of each embodiment of the present invention.

Claims

1. A method for preparing a high-performance sulfide electrolyte, characterized in that: include: mixing the original sulfide and the lithium salt to obtain a mixture; pressing the mixture into a sheet-like mixed solid; The flaky mixed solid is subjected to heat treatment and then subjected to grinding treatment to obtain a high-performance sulfide electrolyte; Wherein, the above steps are all carried out under an inert atmosphere.

2. The preparation method according to claim 1, characterized in that: The original sulfide electrolyte is selected from lithium argyrodite electrolyte (Li6PS5Cl or Li6PS5Br), lithium germanium phosphorus sulfur electrolyte (Li 12 GeP2S 10 or Li 12 SiP2S 10 ), glass ceramic electrolyte (Li7P3S 11 Or Li3PS4), wherein the lithium salt is a halogen lithium salt.

3. The preparation method according to claim 2, wherein the lithium salt is one or more of lithium chloride, lithium fluoride, lithium bromide, and lithium iodide.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the mixture, the molar percentage of the original sulfide electrolyte is 25% to 91%, and the molar percentage of the lithium salt is 19% to 75%.

5. The preparation method according to claim 4, characterized in that: In the mixture, the molar percentage of the original sulfide electrolyte is 33.3% to 66.7%, and the molar percentage of the lithium salt is 33.3% to 66.7%.

6. According to the preparation method of claim 1, the mixing method of the original sulfide and the lithium salt comprises ball milling, the ball milling speed is ≥100 rpm / min, and the time is ≥20 minutes.

7. The preparation method according to claim 1, characterized in that: The pressing pressure of the mixture is 100-500Mpa.

8. The preparation method according to claim 1, characterized in that: The mixed solid heat treatment temperature is 200-600° C., and the treatment time is 0.5-6 hours.

9. A high performance sulfide electrolyte prepared according to any one of the preparation methods of claims 1-8.

10. An all-solid-state battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the high-performance sulfide electrolyte according to claim 9.

Citation Information

Patent Citations

  • Solid electrolyte material and preparation method and application thereof

    CN117497836A

  • Lithium ion solid conductor stable on metal lithium, preparation method of lithium ion solid conductor, and full-solid lithium secondary battery

    CN105140560A

  • Preparation method and preparation mold of all-solid lithium-sulfur battery

    CN109638360A

  • Preparation method for all-solid-state battery material lithium germanium phosphorus sulfide

    CN113851700A

  • Sulfide solid electrolyte and application thereof

    CN114039087A